Minute Ventilation During Spontaneous Breathing, High-Intensity Noninvasive Positive Pressure Ventilation and Intelligent Volume Assured Pressure Support in Hypercapnic COPD. (1st February 2014) - Ekkernkamp, Emelie; Kabitz, Hans-Joachim; Walker, David J.; Schmoor, Claudia; Storre, Jan H.; Windisch, Wolfram; Dreher, Michael
Abstract: Background: High-intensity noninvasive positive pressure ventilation (HI-NPPV) is an effective treatment option in patients with stable hypercapnic chronic obstructive pulmonary disease (COPD). However, the effect of HI-NPPV compared with spontaneous breathing (SB) on minute ventilation (MV) in patients receiving long-term treatment remains to be determined. This study compared MV during HI-NPPV and SB. In addition, the ability of intelligent volume assured pressure support (iVAPS) to increase MV to the same extent as HI-NPPV was determined. Methods: Daytime pneumotachographic measurements were performed during SB, HI-NPPV and iVAPS. Results: Twenty-seven stable hypercapnic COPD patients (mean FEV1 34 ± 15% predicted) who had been treated with HI-NPPV for a median of 22 months (interquartile range 8.5–84 months) were enrolled. Mean MV was 9.5 ± 1.7 L/min during SB and 12.1 ± 2.8 L/min during HI-NPPV, an increase of 2.5 L/min (95% CI [1.5–3.6] p < 0.001), or 26%. MV during iVAPS was 11.7 ± 3.6 L/min, an increase of 1.8 L/min (95%CI [0.7–3.0], p = 0.003) compared with SB. There was no difference in MV between HI-NPPV and iVAPS ( p = 0.25). Conclusion: Long-term HI-NPPV increased MV by an average of 26% compared with SB in stable hypercapnic COPD patients. A similar increase in MV was observed during use of iVAPS.